Influência do laser de baixa intensidade no perfil de expressão dos fatores de apoptose BCL2, BAX e CASPASE 3 clivada após infarto do miocárdio em ratos - Pires, Juliana de Almeida (2016)
Members of the Bcl -2 family are important apoptotic regulators. The Bcl -2 protein can act by activating or repressing apoptosis and may contribute to the emergence of diseases or protect the heart from various heart diseases, respectively. Caspase -3 is an effector protease which cleavage promotes changes that result in cell death. Modulation of apoptotic factors, generated by coronary occlusion and subsequent cell death, after the application of low intensity laser is little studied yet. Using an experimental model, 15 Wistar rats (200-280g) were subjected to myocardial infarction by coronary artery occlusion and randomized into three groups: control (control rats); IM (infarcted rats); IM + Laser (infarcted rats and irradiated with laser). In IM + Laser Group, the infarcted area was treated with laser (λ 660 nm, 15 mW, 60 seconds, irradiated area 0.785 cm2, energy density 22,5 J/cm2 and energy delivered 1,1 Joules) after coronary occlusion. The messenger RNAs of Bax and Bcl2 were quantified by PCR - Real Time (Sybr Green). The Western blotting procedure was conducted to evaluate the protein expression of Bax, Bcl2 and caspase 3. Was observed an increase in gene expression and protein of Bcl2 in IM + Laser group when compared to the IM group (p≤0,05), however no significant difference in gene expression of Bax was found. There was a decrease in the expression of cleaved caspase3 the IM group + Laser in relation to the infarcted group. Our results support the hypothesis that low level lasertherapy can stimulate cell survival after a heart attack, possibly by reducing apoptosis of viable area of the heart to maintain cardiac homeostasis after infarction